2011
DOI: 10.1098/rstb.2010.0190
|View full text |Cite
|
Sign up to set email alerts
|

Underwater linear polarization: physical limitations to biological functions

Abstract: Polarization sensitivity is documented in a range of marine animals. The variety of tasks for which animals can use this sensitivity, and the range over which they do so, are confined by the visual systems of these animals and by the propagation of the polarization information in the aquatic environment. We examine the environmental physical constraints in an attempt to reveal the depth, range and other limitations to the use of polarization sensitivity by marine animals. In clear oceanic waters, navigation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…The angle of polarization describes the predominant direction in which the electric field of the light oscillates, while the degree of polarization defines the extent to which waves oscillate at the same angle. Underwater, differential sensitivity to either angle or degree of polarization has several fundamental advantages over other forms of visual information (Cronin et al, 2003a;Cronin et al, 2003b;Cronin et al, 2009;Shashar et al, 2011). For instance, in shallow, clear marine waters, the intensity and spectral composition of the downwelling light can vary dramatically, both as a function of the time of day, and because of environmental factors such as turbidity (Cronin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The angle of polarization describes the predominant direction in which the electric field of the light oscillates, while the degree of polarization defines the extent to which waves oscillate at the same angle. Underwater, differential sensitivity to either angle or degree of polarization has several fundamental advantages over other forms of visual information (Cronin et al, 2003a;Cronin et al, 2003b;Cronin et al, 2009;Shashar et al, 2011). For instance, in shallow, clear marine waters, the intensity and spectral composition of the downwelling light can vary dramatically, both as a function of the time of day, and because of environmental factors such as turbidity (Cronin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in shallow, clear marine waters, the intensity and spectral composition of the downwelling light can vary dramatically, both as a function of the time of day, and because of environmental factors such as turbidity (Cronin et al, 2014). In such changing conditions, the polarization of light remains more constant than other visual dimensions over short ranges (Waterman, 1954;Cronin, 2001), which renders it a reliable provider of information (Shashar et al, 2011;Johnsen et al, 2011). Previous research in this field has focused on either the underlying retinal mechanisms of polarization sensitivity (for reviews, see Horváth and Varjú, 2004;Roberts et al, 2011) or the optical mechanisms by which polarization and multi-component polarization and/or colour signals are produced (Chiou et al, 2005;Mäthger and Hanlon, 2006;Chiou et al, 2007;Mäthger et al, 2009;Cronin et al, 2009).…”
mentioning
confidence: 99%
“…Most commonly they are used for navigation and habitat or ovipositor site detection, as well as for finding mates. In aquatic habitats, animals such as certain fish, lobster, crabs, crayfish, mantis shrimp and cephalopods have been found to use polarization sensitivity for communication, to improve the visual contrast of their surroundings, or to detect prey (Horváth and Varjú, 2004;Shashar et al, 2011;Wehner, 2001). Although it has been suggested that polarization vision for contrast enhancement and prey detection could also play a role in insect visual systems (Schneider and Langer, 1969;Trujillo-Cenóz and Bernard, 1972;Horváth and Varjú, 2004), to the best of our knowledge, this has never been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Underwater polarization can also be used for navigation under restricted conditions as proven by Lerner et al [67] and Shashar et al [68]. Specialized ultraviolet receptors in the retina allow fishes to see a polarized pattern [69].…”
Section: Polarization Detectors In Animal Visionmentioning
confidence: 99%